Acute retinal pigment epitheliitis and dosimetric follow-up: a case report - Tetiana Babenko; Pavlo Fedirko; Stanislav Saksonov; Iryna Shevchenko; Māra Pilmane; Valentyna Vasylenko; Oleksandra Korobova; Natalia Garkava; Mykola Kuriata (Ukrainian Society of Ophthalmologists, 2024)
Acute retinal pigment epitheliitis (ARPE; also known as Krill disease), a disease first described in the nineteen seventies, is characterized by fine pigment stippling in the macular area, surrounded by hypopigmented halo. The etiology of the disease is not yet known. The patient reported that he used to eat berries picked from the forest in the radioactive contaminated area in late June to early July, 2023. He complained of transient metamorphopsia and reduced vision in the left eye, and received eye examination including optical coherence tomography, general check-up, blood cell counts and whole body radionuclide content study. He was diagnosed with bilateral APRE. On the basis of measurements with the expert whole-body counter, the wholebody burden of Сs-137 for the patient was 505 Bq, and the estimated annual effective dose from internal radiation was 0.011 mSv/y. The estimated dose value was substantially lower than the basic dose limit for the population of 1 mSv/y as per requirement of the Law of Ukraine. Because APRE is a rare disease with an unknown etiology, careful attention deserves to be given to the finding of the disease in a patient who has sustained short-term exposure to ionizing radiation due to the incorporation of Сs-137 into his body tissues. For the first time it has become possible to assess adequately doses from internal radiation in a patient with APRE, which will allow to optimize efforts for further research on the etiology of this rare disorder.